Desarrollo y operación de sensores para control directo y continúo en plantas de beneficio de minerales y en la restauración del medio ambiente. - Kawatra, Komas (My University, 1998)
In many coal flotation operations, a significant amount of apparently liberated pyrite is seen to report to the froth, thus raising the sulfur content of the clean product and reducing its economic value.
Keywords: mechanical; analysis; circuits; sensors; process